Does Culture Influence Tax Morale? Evidence from Different European Countries - Benno Torgler; Friedrich Schneider (Center for Research in Economics, Management and the Arts (CREMA), 2004)
There is considerable evidence that enforcement efforts cannot fully explain the high degree of tax compliance. Previous studies have found differences in compliance behaviour across cultures. Novel in this paper is to investigate the impact of culture differences within a country rather than between countries. Thus, the main purpose of the paper is to see how culture affects tax morale, using World Values Survey (WVS) and European Values Survey (EVS) data. The empirical findings focus individually on Switzerland, Belgium and Spain, countries with a certain cultural variety. In general, the results indicate that the cultural background seems not to have a strong effect on tax morale within a country. However, there is evidence that there is a strong interaction between culture and institutions, which has a strong impact on tax morale.
Keywords: H26; H73; 330; Tax Morale; Tax Compliance; Tax Evasion; Culture